Induction of platelet-derived growth factor gene expression during megakaryoblastic and monocytic differentiation of human leukemia cell lines. - Alitalo, R (1987)
Platelet-derived growth factor (PDGF) is one of the most important polypeptide growth factors in human serum. It is composed of two polypeptide chains linked by disulfide bonds. The B-chain is encoded by the c-sis proto-oncogene, which is expressed in several malignant and non-malignant cells including K562 cells differentiating towards megakaryoblasts. Expression of the A-chain has been reported to occur in human solid tumor cell lines independently of c-sis expression. We report here the non-coordinate expression of the A- and B-chains in human leukemia cell lines. The PDGF-A and B-chain (c-sis) RNA expression as well as secretion of PDGF polypeptides are induced in the K562 cell line upon induction of megakaryoblastic differentiation with 12-O-tetradecanoyl phorbol-13-acetate (TPA) whereas erythroid differentiation induced with sodium butyrate is accompanied by c-sis expression only. Simultaneously with megakaryoblastic differentiation the RNA level for another platelet protein, the transforming growth factor-beta was also increased, but in a complex manner. The promyelocytic leukemia cell line HL-60 does not express PDGF-A RNA, whereas the promonocytic cell line U937 does. Preferential induction of the A-chain RNA is obtained in both cell lines after treatment with TPA which causes monocytic differentiation. PDGF-A expression in HL-60 cells is also observed after treatment with the tumor necrosis factor-alpha but granulocytic differentiation of HL-60 cells induced with dimethyl sulfoxide or the granulocyte colony-stimulating factor is not associated with PDGF gene expression.